Identifying the effects of corruption perception on the relationship between international trade and logistics performance in developing countries - Avni Zafer Acar; Karahan Kara (Business, Management and Economics Engineering (BMEE), 2023)
Purpose - logistics creates a strategic effect by playing a facilitating role in international trade, which has a significant impact on the economic performance of countries. Logistics performance and corruption play an influential role in determining the trade efficiency levels of developing countries. There are two purposes in this research. First purpose is to determine the international trade efficiency level of developing countries based on logistics performance. The second purpose is to determine the efficiency level of trade based on both logistics performance and corruption levels. Research methodology - output-oriented data envelopment analysis (DEA) has been applied in the research. The research covers the years 2012-2020. The sample area is developing countries. Findings - countries with full efficiency levels in 2012-2020 have been determined according to both logistics performance and corruption scores. Research limitations - the research covers the years 2012-2020. The sample area is developing countries. Practical implications - the reduction of corruption levels in some developing countries is an important factor in increasing the level of international trade efficiency. Originality/Value - this research highlights the role of corruption in the relationship between trade and logistics performance.
Keywords: D73; O11; C30; 330; corruption; data envelopment analysis; developing countries; international trade; logistics performance